A Heterogeneously Expressed Gene Family Modulates the Biofilm Architecture and Hypoxic Growth of Aspergillus fumigatus - Caitlin H. Kowalski (American Society for Microbiology, 2021)

(untitled)
The manipulation of microbial biofilms in industrial and clinical applications remains a difficult task. The problem is particularly acute with regard to filamentous fungal biofilms for which molecular mechanisms of biofilm formation, maintenance, and function are only just being elucidated.